Dissemination of social accounting information: A bibliometric review - Margarida Rodrigues; Maria do Céu Alves; Cidália Oliveira; Vera Teixeira Vale; José Vale; Rui Silva (Economies, 2021)
The discussion in recent decades about sustainable development issues has given rise to a new accounting dimension: social accounting. Currently, this issue remains an emerging theme. Although there are some studies and literature reviews, none include disclosure of social accounting information or the analysis of research paradigms. This article reviews the research on social accounting disclosure and tries to answer the following research questions: What research streams have been followed? Which theories and research paradigms have been used? The search for articles to be included in the literature review was performed through the Web of Science. The 126 articles obtained were later analyzed using Bibliometrix software. Results expose the growing interest in this theme and identify three distinct research lines (three clusters): Cluster 1-Social accounting disclosures, Cluster 2-Legitimacy vs. disclosure of social accounting, and Cluster 3-Motivations for disclosure of social accounting. The main contribute of this article resides, on the one hand, in the fact that no literature review articles have been found that include the theme of the disclosure of information on social accounting and, on the other hand, the treatment of data has been done with innovative software, an R package for bibliometric and co-citation analysis called Bibliometrix. As well as mapping the literature, another theoretical contribution of this study was identifying the main research approaches used in the studies. Within the paradigmatic plurality of social accounting research, the results suggest that social accounting research can also be critically addressed when addressing the sustainability challenges posed by climate change or carbon emissions, among many other aspects. This study is, to our knowledge, the first bibliometric review done about social accounting information disclosure.
Keywords: 330; social accounting; social and environmental accounting; social reporting; voluntary disclosure